Peran Perguruan Tinggi Pesantren dalam Menjawab Tantangan Global: Studi Kasus Universitas KH Abdul Chalim Mojokerto - Muhammad Farih; Ita Putri Magfiroh (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to analyze the role of Islamic higher education institutions based on pesantren in responding to global challenges through a case study at Universitas KH. Abdul Chalim (UAC) Pacet Mojokerto. Using a qualitative field research approach, data were collected through interviews, observation, and documentation involving university leaders, lecturers, and students. The results show that UAC has successfully integrated pesantren values into higher education through an academic curriculum based on Ahlussunnah wal Jama’ah principles combined with modern scientific disciplines. The integration is implemented through structured spiritual development, character building, and digital-based learning innovations. UAC also strengthens its global competitiveness through research collaborations, international conferences, and academic partnerships with institutions in Egypt and Morocco. This study concludes that the pesantren-based higher education model applied by UAC can be an effective prototype for developing modern Islamic education that balances faith (IMTAQ) and science (IPTEK) to face the demands of globalization.